2018
DOI: 10.1007/s40520-018-1033-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of length of stay in hospital among older patients

Abstract: A useful estimate of outcome and LOS can be made by constructing a predictive equation from information on hospital admission, to provide evidence-based guidance for resource requirements and discharge planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
1
36
1
Order By: Relevance
“…The association between NHFS and prolonged LOS in hospital observed in our study mirrors those reported by Moppett et al [11] who showed increasing NHFS was related inversely to the proportions of patients being discharged early back to their own home. The extra days spent in hospital by patients with NHFS in the intermediate (2 days) or in the high risk (4 days) groups are similar to those observed in patients admitted with cognitive impairment or delirium [4]. Our observations of the association between high NHFS with discharge to residential/nursing care are also consistent with the findings of a negative correlation between NHFS and eventual return-to-home by Moppett et al [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association between NHFS and prolonged LOS in hospital observed in our study mirrors those reported by Moppett et al [11] who showed increasing NHFS was related inversely to the proportions of patients being discharged early back to their own home. The extra days spent in hospital by patients with NHFS in the intermediate (2 days) or in the high risk (4 days) groups are similar to those observed in patients admitted with cognitive impairment or delirium [4]. Our observations of the association between high NHFS with discharge to residential/nursing care are also consistent with the findings of a negative correlation between NHFS and eventual return-to-home by Moppett et al [11].…”
Section: Discussionsupporting
confidence: 89%
“…Through our participation in the National Hip Fracture Database (NHFD) Audit Programme [4,12,13], data were prospectively collected by a Trauma Coordinator for patients admitted with a hip fracture from time of admission to discharge. The data comprised clinical characteristics and care quality, mobility within 1 day after hip surgery, LOS during admission, and discharge destination.…”
Section: Measurementmentioning
confidence: 99%
“…They reported in-patient prevalences for evidence of delirium were 20.6% in orthopaedics units, 21.2% in general internal medicine units, 24.7% in geriatrics units and 28.5% in neurology units. Prolonged LOS and mortality, as well as residential/nursing care, are high among older patients; especially those admitted with hip fractures [16] with enormous burdens to both patients and healthcare systems [17,18]. Our study observed that just over one-half of patients returned to their own home directly after discharge while more than a third of patients were transferred to rehabilitation units.…”
Section: Los Increased By Three and Six Days For Patients With 4at Smentioning
confidence: 64%
“…Several studies have identified factors associated with protracted hospitalization, but many of these have focused on targeted patient populations [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] or involved data collected at a single centre [ 13 , 18 , 19 , 23 , 24 , 28 , 29 , 31 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] Understanding the factors that contribute to prolonged hospitalization in a broader patient cohort may guide the development of interventions that target at risk patients, improve overall care, and reduce resource utilisation.…”
Section: Introductionmentioning
confidence: 99%